Duplex project management maturity model (DPM3) key to organisational performance - Gan, Robert Chee Choong (2022)
Project management maturity models (PM3) are generic project management tools, designed to measure the approximate balance state of organisation’s capability and capacity to manage projects, programmes and portfolios. These tools are designed to be generic in form, free of technical jargons and structured at a level that is high enough for users to see the big picture and then adapt to tailor to their appropriate level of rigour thus serving diverse organisations.